Fluxomics of the Eastern Oyster for Environmental Stress Studies - Tikunov, Andrey P. (MDPI, 2014)
The metabolism of 2-(13)C/(15)N-glycine and U-(13)C-glucose was determined in four tissue blocks (adductor muscle, stomach and digestive gland, mantle, and gills) of the Eastern oyster (Crassostrea virginica) using proton ((1)H) and carbon-13 ((13)C) nuclear magnetic resonance (NMR) spectroscopy. The oysters were treated in aerated seawater with three treatments (5.5 mM U-(13)C-glucose, 2.7 mM 2-(13)C/(15)N-glycine, and 5.5 mM U-(13)C-glucose plus 2.7 mM 2-(13)C/(15)N-glycine) and the relative mass balance and (13)C fractional enrichments were determined in the four tissue blocks. In all tissues, glycine was metabolized by the glycine cycle forming serine exclusively in the mitochondria by the glycine cleavage system forming 2,3-(13)C-serine. In muscle, a minor amount of serine-derived pyruvate entered the Krebs cycle as substantiated by detection of a trace of 2,3-(13)C-aspartate. In all tissues, U-(13)C-glucose formed glycogen by glycogen synthesis, alanine by glycolysis, and glutamate and aspartate through the Krebs cycle. Alanine was formed exclusively from glucose via alanine transaminase and not glycine via alanine-glyoxylate transaminase. Based on isotopomer analysis, pyruvate carboxylase and pyruvate dehydrogenase appeared to be equal points for pyruvate entry into the Krebs cycle. In the 5.5 mM U-(13)C-glucose plus 2.7 mM 2-(13)C/(15)N-glycine emergence treatment used to simulate 12 h of “low tide”, oysters accumulated more (13)C-labeled metabolites, including both anaerobic glycolytic and aerobic Krebs cycle intermediates. The aerobic metabolites could be the biochemical result of the gaping behavior of mollusks during emergence. The change in tissue distribution and mass balance of (13)C-labeled nutrients (U-(13)C-glucose and 2-(13)C/(15)N-glycine) provides the basis for a new quantitative fluxomic method for elucidating sub-lethal environmental effects in marine organisms called whole body mass balance phenotyping (WoMBaP).